Puncture position on wind turbine blades and arc path evolution under lightning strikes. (15th May 2017) - Yan, Jiangyan; Li, Qingmin; Guo, Zixin; Ma, Yufei; Wang, Guozheng; Zhang, Li; Yan, Joseph D.
Abstract: Wind turbine blades are easy to get lightning strikes, which is calling more and more attention in recent years. Impulse voltage was applied on different blade structures and materials to study the puncture position distribution and the arc path inside the blade chamber. The experimental results reflected that most puncture points were located in the sandwich structure and thinner glass fiber cover. There was no obvious connection between puncture position, voltage polarities, and voltage peak values as to the experiment in this paper. However, the surface moisture and the experimental electrode position had significant influence for the puncture position. Arc paths inside the blade chamber considering different puncture positions were also studied. It can be concluded from the experiments that the arc usually consisted of surface-arc part and the air-arc part, in which the length of each part varied with the puncture position, voltage peak values and polarities. The research findings revealed the weak areas on typical blade and as well as the possible arc paths inside the sealed chamber, which will offer guidance for the lightning protection design of blade materials and the whole structure. Graphical abstract: Highlights: The wind turbine blades usually get breakdown on the back sandwich or the thin glass fiber. Long arc paths may exist if the blade width is large enough. Lightning induced arc is characterized as a short surface path on the top blade. Water moisture of the blade surface increases the risk of lightning strikes.